Global insights from patients, providers, and staff on challenges and solutions in managing neovascular age-related macular degeneration - Loewenstein, Anat; Sylvanowicz, Michelle; Amoaku, Winfried M.; Aslam, Tariq; Cheung, Chui Ming Gemmy; Eldem, Bora; Finger, Robert P.; Gale, Richard P.; Kodjikian, Laurent; Koh, Adrian; Korobelnik, Jean-François; Lin, Xiaofeng; et al. (Ophthalmology and therapy, 2025)
Introduction Neovascular age-related macular degeneration is a global public-health concern, associated with a considerable burden to individuals, healthcare systems, and society. The objective of this study was to understand different perspectives on the challenges associated with the clinical management of neovascular age-related macular degeneration, which could elucidate measures to comprehensively improve clinical care and outcomes. Methods A survey was carried out of patients with neovascular age-related macular degeneration, their providers, and clinic staff in 77 clinics across 24 countries on six continents, from a diverse range of healthcare systems, settings, and reimbursement models. Surveys comprised a series of single/multiple-response questions completed anonymously. Data gathered included patient personal characteristics, appointment attendance challenges, treatment experiences, and opportunities to improve support. Provider and clinic staff surveys asked similar questions about their perspectives; clinic characteristics were also captured. Results There were 6425 responses; 4558 patients with neovascular age-related macular degeneration, 659 providers, and 1208 clinic staff. Challenges identified included concern about patient burden to family/friends, high frequency of treatment, difficulties in traveling to appointments, long waiting times, and insufficient comprehension of neovascular age-related macular degeneration. Participants identified logistical (improved financial assistance with treatment and out-of-pocket costs, and appointment reminders), operational (addressing clinic set up to reduce waiting times and improving the amount of time providers spend with patients), and educational (improving quality and provision of patient information and expectation-setting) opportunities to improve care. Conclusions The wealth of data generated by this global survey highlights the breadth of challenges associated with clinical management of patients with neovascular age-related macular degeneration. Addressing the opportunities raised could improve patient adherence to treatment and potentially outcomes, reduce appointment burden, and increase clinic capacity.
Online veröffentlicht: 14. Dezember 2024
Gesehen am 08.05.2025